Use of bodily-kinesthetic intelligence theory to improve the creative learning of the english language in students of 1st EGB at unidad educativa bilingue instituto particular Abdón Calderón - Almeida Uzho, Stefany Paola (2016)
This research i nvolves the application of Bodily Ki nesthetic Intelligence Theory to improve the creati ve learni ng in students of 1ST EGB at Unidad Educativa Instituto Particular Bilingüe Abdón Calderón. To structure this project in its theoretical basis we have relied on multiple inputs from different authors who studied the issue and their contributions were of great importance to support our research…..